PENGARUH KEPEMIMPINAN KEPALA SEKOLAH DENGAN MEDIASI MOTIVASI KERJA GURU DALAM MENINGKATKAN KINERJA GURU SEKOLAH DASAR DI KECAMATAN TENGARAN KABUPATEN SEMARANG - Enggar Jati Pratikto; Yeri Sutopo; Sarwi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
In the era of globalization and rapid technological development, the world of education faces increasingly complex challenges. Teachers are not only required to master learning materials, but also be able to adapt to changes, utilize technology, and form competitive student characters. In this case, the principal has a strategic role as an education leader, especially in creating a work environment that supports and motivates teachers to achieve optimal performance. The teacher's work motivation itself is a psychological factor that affects the success of the teaching and learning process. This study aims to analyze the influence of school principals' leadership on teacher performance by considering the mediating role of work motivation in elementary schools in Tengaran District, Semarang Regency. The quantitative approach is used through path analysis to see the direct and indirect relationships between variables. The results of the study show that the leadership of school principals has a significant effect on work motivation and directly also on teacher performance. Teachers' work motivation also contributes significantly to performance, as well as mediating the influence of the principal's leadership on performance with a total influence of 0.723. These findings confirm the importance of effective leadership and high motivation in improving teacher performance. This research provides implications for education policymakers and school principals to develop transformative leadership and strategies to increase work motivation, in order to encourage the achievement of optimal teacher performance and improve the quality of basic education.